Under-Five Mortality and Associated Risk Factors in Rural Settings of Ethiopia: Evidences from 2016 Ethiopian Demographic and Health Survey - Shewayiref Geremew Gebremichael; Setegn Muche Fenta (Advances in Public Health)
Background. Evidence shows that in Ethiopia, a gradual decrease of under-five mortality is observed, but it is still high in the rural settings of the country. We are motivated to investigate the socioeconomic, demographic, maternal and paternal, and child-related associated risk factors of under-five mortality given birth from rural resident mothers. Methods. Demographic and Health Survey data from Ethiopia (2016) were used for analysis. The chi-square test of association and logistic regression were used to determine the associated risk factors of under-five children mortality. Study Settings. Rural Ethiopia. Results. Secondary school and above completed fathers (AOR = 0.77; 95% CI: 0.63–0.94) and primary school completed mothers (AOR = 0.82; 95% CI: 0.72–0.93); multiple twin child (AOR = 4.50; 95% CI: 3.38–5.98); public sector delivery (AOR = 0.65; 95% CI: 0.55–0.76); had working of mother (AOR = 1.28; 95% CI: 1.16–1.42) and of father (AOR = 1.45; 95% CI: 1.25–1.69); mothers aged above 16 at first birth (AOR = 0.41; 95% CI: 0.37–0.45); breastfeeding (AOR = 0.60; 95% CI: 0.55–0.66); birth order of 2-3 (AOR = 1.18; 95% CI: 1.02–1.37); religious belief of Muslim (AOR = 1.20; 95% CI: 1.02–1.41); users of contraceptive method (AOR = 0.80; 95% CI: 0.71–0.90); vaccinated child (AOR = 0.52; 95% CI: 0.46–0.60); family size of 4–6 (AOR = 0.74; 95% CI: 0.63–0.86) and of seven and above (AOR = 0.44; 95% CI: 0.36–0.52); mother’s age group: aged 20–29 (AOR = 3.88; 95% CI: 3.08–4.90), aged 30–39 (AOR = 16.29; 95% CI: 12.66–20.96), and aged 40 and above (AOR = 55.97; 95% CI: 42.27–74.13); number of antenatal visits: 1–3 visits (AOR = 0.50; 95% CI: 0.43–0.58), and four and above visits (AOR = 0.46; 95% CI: 0.39–0.54); and preceding birth interval of 25–36 months (AOR = 0.55; 95% CI: 0.48–0.62) and above 36 months (AOR = 0.30; 95% CI: 0.26–0.34) are significant determinant factors of under-five mortality in rural settings. Conclusions. Differences in regions, educated parents, born in singleton, public sector delivery, nonavailability of occupation of parents, mothers older than 16 at first birth, breastfeeding, use of a contraceptive method, child vaccination, higher number of family size, repeated antenatal visits, and preceding birth interval play a significant role regarding the survival of under-five children. These, among other differences, should be addressed decisively as part of any upcoming strategic interventions to improve the survival of children in line with the target of 2030 Sustainable Development Goals (SDGs).